2021
DOI: 10.3390/cancers13184569
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Hypermethylation Promotes the Binding of Transcription Factor NFATc1, Triggering Oncogenic Gene Activation in Pancreatic Cancer

Abstract: Studies have indicated that some genes involved in carcinogenesis are highly methylated in their promoter regions but nevertheless strongly transcribed. It has been proposed that transcription factors could bind specifically to methylated promoters and trigger transcription. We looked at this rather comprehensively for pancreatic ductal adenocarcinoma (PDAC) and studied some cases in more detail. Some 2% of regulated genes in PDAC exhibited higher transcription coupled to promoter hypermethylation in compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Furthermore, NFAT4 knockdown, and treatment with CsA and FK506 impaired the growth of NPC cells. Other studies have also supported the critical role of the NFAT pathway in cancer progression ( Mancini and Toker 2009 ; Kim et al, 2019 ; Wu et al, 2021 ). Consistent with this, NFAT4 expression was higher in NPC tissues, and correlated positively with that of TRPV4.…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, NFAT4 knockdown, and treatment with CsA and FK506 impaired the growth of NPC cells. Other studies have also supported the critical role of the NFAT pathway in cancer progression ( Mancini and Toker 2009 ; Kim et al, 2019 ; Wu et al, 2021 ). Consistent with this, NFAT4 expression was higher in NPC tissues, and correlated positively with that of TRPV4.…”
Section: Discussionmentioning
confidence: 73%
“…Hence, the main focus in epigenetic pharmacology was on developing strategies that will inhibit DNA methylation and remove aberrant methylation marks from tumor suppressor genes to produce anti-cancer effects. However, technological advances allowed for genome-wide studies of DNA methylation patterns in cancer, which showed that some hypermethylated promoters are actually associated with active transcription rather than silencing [ 7 ]. In pancreatic cancer, this phenomenon was mechanistically explained by the preferential binding of the NFATc1 transcription factor to hypermethylated DNA, followed by the activation of the transcriptional machinery [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, technological advances allowed for genome-wide studies of DNA methylation patterns in cancer, which showed that some hypermethylated promoters are actually associated with active transcription rather than silencing [ 7 ]. In pancreatic cancer, this phenomenon was mechanistically explained by the preferential binding of the NFATc1 transcription factor to hypermethylated DNA, followed by the activation of the transcriptional machinery [ 7 ]. Recent decades of genome-wide studies of the DNA methylation landscape in cancer also show that DNA hypomethylation of promoters and other gene regulatory regions, like enhancers, is as prevalent in cancer as hypermethylation [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%